National Role Delineation Study of the Board Certification for Advanced Diabetes Management: Evidence-Based Support of the New Test Content Outline. (October 2015) - Schreiner, Barb; Kolb, Leslie E.; O'Brian, Catherine A.; Carroll, Sarah; Lipman, Ruth D.
Purpose: The purpose of this comprehensive role delineation study of the Board Certification for Advanced Diabetes Management (BC-ADM) examination was to ensure its content validity. Method: The comprehensive role delineation study was conducted in 3 phases. In the first phase, a panel of 12 currently credentialed BC-ADM subject matter experts produced a list of practice domains, a unique set of content subdomains for each, and a series of knowledge statements for every subdomain. In the second phase, a validation study survey consisting of 3 sections was created. The first section was to rate each subdomain on three factors: criticality, frequency, and point in career at which knowledge is first used. The second section asked respondents to estimate the percentage of the examination to dedicate to the four domains. The third section captured demographic information of the respondents. A total of 667 BC-ADMs and 18 physicians were invited to take the survey. In the third phase, the subject matter expert panel analyzed the survey results and determined the weight that the domains and subdomains should have on the 150-item BC-ADM examination. Results: Final domain weights and the corresponding number of items for the BC-ADM examination are provided in this report; these constitute the BC-ADM examination blueprint. Conclusions: The national role delineation study reported here for the BC-ADM examination ensures that it is reflective of the current practice and required knowledge of the advanced diabetes manager.